IMPLEMENTASI PENDEKATAN KONSTRUKTIVISTIK DALAM PEMBELAJARAN PAI BERBASIS KURIKULUM MERDEKA DI SMP PLUS JA-ALHAQ KOTA BENGKULU - Azidnia; Hardin, Novianti; Asiyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of the constructivist approach in Islamic Religious Education (PAI) learning under the Independent Curriculum at SMP Plus Ja-alHaq, Bengkulu City. PAI learning in schools is still often dominated by teacher-centered lecture methods, resulting in relatively limited student engagement in the learning process. This study used a qualitative descriptive method with data collection techniques in the form of observation and literature review. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results show that the application of constructivist strategies such as Problem-Based Learning (PBL), group discussions, project-based learning, and the use of digital technology can increase student active engagement in learning. Students become more reflective, critical, and able to teach Islam in a more contextual way with everyday life. However, the implementation of this approach still faces several obstacles, including limited teacher preparation time, suboptimal learning facilities, and differences in student learning abilities and cultures, who are still accustomed to passive learning patterns. Therefore, support from the school and improvement of teacher competency are essential to optimize the implementation of the constructivist approach in PAI learning based on the Independent Curriculum.